Risen indeed a historical investigation into the resurrection of Jesus - Habermas, Gary R. 1950- (Ashland Lexham Press, 2021)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Acknowledgments -- Introduction -- My Religious Doubts -- The Minimal Facts Methodology in Resurrection Research -- The Third Quest for the Historical Jesus -- Resurrection Studies from 1975 to the Present -- Major Resurrection Trends in the Early Twentieth Century -- Ongoing Resurrection Trends -- The Minimal Facts Argument: Spotlighting the Best Data -- A Last Major Area of Study -- Conclusion -- Part 1: Approaching the Question of the Resurrection of Jesus -- Chapter I: The Present State of the Question -- A. Theology and the Resurrection -- 1. The Importance of the Resurrection -- 2. The Contemporary Theological Approach to the Resurrection -- B. History, Philosophy, and the Resurrection -- 1. History and the Resurrection -- 2. Philosophy and the Resurrection -- Chapter II: The Possibility of Miracles Today -- A. Miracle and Myth -- 1. A Definition of Miracle -- 2. A Definition of Myth -- B. Twentieth-Century Science and Miracles -- 1. Introduction -- 2. Some Principles of Physics -- 3. Miracles -- Chapter III: History and Miracles -- A. A Concept of History -- B. Investigating the Historical Events -- 1. Historical Research and Investigation -- 2. The Resurrection and Historical Investigation -- Chapter IV: Reason and Faith -- A. Reason and Faith: Definitions -- B. Reason and Faith: Scholarly Views -- Part 2: Possible Solutions to the Question of the Resurrection of Jesus -- Chapter V: Possibility Number One: That the Resurrection Did Not Occur -- A. David Hume: An Introduction -- B. David Hume's Argument and a Critique -- Chapter VI: Possibility Number One: Other Similar Views -- A. Heinrich Paulus -- B. David Strauss -- C. Otto Pfleiderer -- Chapter VII: Possibility Number Two: That the Resurrection Did Occur, but that It Cannot Be Demonstrated.
Description based on publisher supplied metadata and other sources
Keywords: Jesus Christ; Apologetics; Electronic books